Model Penyelesaian Alternatif Perkara Pidana Pembunuhan Biasa menurut Hukum Islam dan Relevansinya dengan Pembaharuan Hukum Pidana Indonesia - Hambali Yusuf; Saifullah Basri (Fakultas Hukum Universitas Islam Indonesia, 2017)
This research is designed to study the model of alternative resolution of crime suit in accordance with the Islamic law that can be used as the model of resolving the crime suit of ordinary assassin in Indonesia. The method of this research was juridical normative method. The result of this research showed that the model of resolution of diyat and apology in Islamic concept are highly relevant and acceptable by Indonesia people. The noble values as a culture of forgiveness and resolving the issue by more emphasizing on deliberation have been highly maintained and developed since a long time age among the ancestors. The ordinary assassin could be solved by forgiving in this case by paying the Tepung Tawar (Malay Custom) as long as the assassin is not related to the public interest..